Ocena potresne ogroženosti stanovanjskih stavb v Sloveniji - Kilar, Vojko (AR. Arhitektura, raziskave, 2004)
The article assesses earthquake vulnerability of residential buildings in Slovenia. Data gathered from the last census of the population, households and housings was used as the starting point, whereby assessment of vulnerability was done from data on year of construction, number of floors, materials used for load bearing structures and year of last renovation. The article starts with a short description of typical time, frames of building construction, marked by historical events and the development of regulations concerning earthquake resistant construction, from which we can estimate their present condition and earthquake resistance. In continuation a detailed categorisation of buildings, based on age, material and number of floors, is presented for the entire housing stock in Slovenia. The conclusion gives estimates of probable earthquake vulnerability of the housing stock, which are joined into three classes: a) not earthquake resistant buildings, b) less earthquake resistant buildings and c) earthquake resistant buildings.
Keywords: stanovanjske zgradbe; potresna ogroženost; Slovenia; Slovenija; 2002